THE EFFECT OF ADDITION OF TOFU WASTE FLOUR TOWARD THE QUALITY CHARACTERISTICS OF CATFISH (Pangasius hypophthalmus) ATOM CRACKERS - Silvia Isma Utari MZ; N. Ira Sari; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was aimed to determine the effect of addition of tofu waste flour and obtain the best amount of tofu waste flour in the processing of catfish (Pangasius hypophthalmus) atoms crackers from the aspect of organoleptic quality and proximate analysis. The experimental method was used in this research with the addition different amount of tofu waste flour into catfish atom crackers which consists of 4 treatment levels i.e. without addition of tofu waste flour as a control (KA0), 10% of tofu waste flour (KA1), 20% of tofu waste flour (KA2), and 30% of tofu waste flour (KA3). The result showed that the addition 10% of tofu waste flour into catfish atom crackers was the best treatment with the characteristics: a light brown color of appearance; tasty, savory and typical tofu flavour; typical aroma of tofu waste balanced with aroma of fish; and solid, compact and crisp texture. Meanwhile for proximate analysis of moisture, protein and fat content was 9.12%, 17.3% and 2.97%, respectively.Key word :atom crackers, catfish, tofu waste flour